Characterization of Ionic Composition in the Submicron Fraction of Urban Aerosol - Sara Padoan; Elena Barbaro; FELTRACCO, MATTEO; Roberta Zangrando; Carlo Barbante; Andrea Gambaro (Società Chimica Italiana, 2018)
Atmospheric particles are polydisperse, varying the diameter of more than four orders of magnitude: from some nanometers (nm) to tens or hundreds of micrometers (µm) (1). Particle size is one of the most important parameters to monitor particles’ behavior in the atmosphere because it indicates the type of source and influences transport and deposition processes. Particle size distribution and concentrations of ionic species are quantified to determine their potential sources of input, chemical evolution and transport (2). The main aim of the present work was to investigate the particle size distribution of ionic compounds (Cl, Br, I, NO3-, MSA, SO42-, PO43- , C2-oxalic acid, C2-glycolic acid, C2-acetic acid, C3-malonic acid, cis-usC4-maleic, trans-usC4-fumaric, C4-succinic acid, αC7-benzoic acid, C5-glutaric acid, hC4-malic acid, C6-adipic acid, C7-pimelic acid, Na+, NH4+, K+and Mg+) in urban aerosol collected atVenice. We used 120 MOUDITM II sampler that permitted to separate particles in 12 dimensionalfractions starting with a diameter greater or equal to 18 µm to a diameter below of 56 nm. The sampling was carried out during the 2016 spring season between March and May. The determination of anionic compounds was performed using ion-chromatography coupled to mass spectrometry (IC-MS), while cationic species were determined through capillary ion chromatography with conductometry (2). The concentration of ionic compounds in the aerosol samples represented the highest percentage of aerosol mass concentration. The study of the ionic composition and their particle size distribution in the analyzed samples has allowed to identify different sources, as well as marine input and anthropogenic contribution. References: 1. P. H. Mcmurry, “A review of atmospheric aerosol measurements ଝ,” vol. 34, 2000. 2. E. Barbaro et al., “Particle size distribution of inorganic and organic ions in coastal and inland Antarctic aerosol,” pp. 2724–2733, 2017.